TANTANGAN SISTEM PENDIDIKAN KONTEMPORER DALAM MENGHADAPI GLOBALISASI DAN KETIMPANGAN AKSES PENDIDIKAN DI ERA SOCIETY 5.0 - Kirana Utami Putri; Yudo Handoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study explores the challenges of contemporary education systems in addressing globalization and disparities in access to education in the Society 5.0 era. The core problem lies in the imbalance of educational opportunities caused by rapid technological development, socio-economic inequality, and uneven distribution of digital infrastructure. The purpose of this research is to identify and analyze these challenges and to formulate strategic solutions based on theoretical and empirical literature. This research uses a literature review method by examining various credible sources such as academic journals, books, and relevant research reports. The results indicate that globalization and digital transformation have significantly influenced educational systems, demanding innovation in learning approaches, policy reform, and the integration of technology in education. However, limited digital access, low levels of digital literacy, and economic disparities remain critical barriers to achieving equitable education. Therefore, strengthening inclusive education policies, expanding technological infrastructure, and enhancing human resource capacity are necessary steps to overcome these challenges and to realize a more equitable and adaptive education system in the Society 5.0 era